NDUFS4, a mitochondrial complex I subunit, is essential for T-cell metabolic fitness and immune function - Shamriz, Oded; Bar-On, Zahala; Yosef, Omri; Cohen-Daniel, Leonor; Sheer, Ayelet; Reuven, Or; Salaymeh, Wajeeh; Saragovi, Amijai; Somech, Raz; Lev, Atar; Mor-Shaked, Hagar; Tal, Yuval; et al. (Frontiers in Immunology, 2026)
IntroductionMitochondrial metabolism is essential for T-cell function, but the roles of individual electron transport chain (ETC) components are unclear. Here, we aimed to explore the role of mitochondrial complex I (CI) subunit NADH:ubiquinone oxidoreductase iron-sulfur protein 4 (NDUFS4) in T-cell metabolic fitness and immunity.MethodsWe used a T cell-specific Ndufs4 knockout mouse model to find that NDUFS4 deficiency disrupts CI function, leading to metabolic and redox imbalances. Additionally, T cells from a patient with Leigh syndrome induced by NDUFS4 loss-of-function were analyzed.ResultsNdufs4-deficient T cells exhibit impaired OXPHOS, reduced respiratory capacity, and increased glycolysis, accompanied by reactive oxygen species (ROS) accumulation and defective TCR-driven activation, including reduced proliferation and cytokine production. In vivo, Ndufs4(-/-) mice show T-cell lymphopenia and impaired humoral and cytotoxic immunity. Importantly, T cells from a single Leigh syndrome patient with an NDUFS4 loss-of-function variant showed similar defects, including impaired activation and proliferation.DiscussionThese findings highlight the importance of NDUFS4 for human immunity and establish a mechanistic link between complex I dysfunction and T-cell immunodeficiency. Our results identify NDUFS4 as a key regulator connecting mitochondrial integrity to adaptive immune function.